Pengaruh Kompetensi Guru terhadap Tingkat Pencapaian Pertumbuhan Perkembangan Anak PAUD di Kabupaten Bengkalis Provinsi Riau - Nurhaida Selian; Desi Arpa (STAIN Bengkalis, 2021)
The early childhood education teacher competence at Bengkalis Recency and STPPA never has result data accurate and valid at Bengkalis, so the researcher interested in the STTPA PAUD and investigating is their influence between the teacher competence toward the student early child standard level of development at Bengkalis Regency. The population in the research by using a random sampling technique 10 % from the total data 50 teachers dan 50 students. And collecting data, the researcher using questioner by google form and calculate by computing statistic inferential. The result of the research is the STTPA for early childhood students in Bengalis is rate standard (medium) and there isn't a significant correlation between the teacher's competence toward the child level development standard at Bengkalis Regency.